All-fiber graphene passively q-switched nanosecond thulium doped fiber laser at 1900 nm - Saidin, Norazlina; Ahmad, Fauzan; Zen, D. I. M.; Hamida, Belal Ahmed; Khan, Sheroz; Ahmad , Harith B.; Dimyati, Kaharudin; Harun, S. W. (2013)
We successfully demonstrated a simple, compact and low cost passive Q-switched Thulium doped fiber laser (TDFL) at long wavelength of 1854.3 nm regions in conjunction with 1552 nm pump excitation. A stable pulse has been generated using graphene film based saturable absorber (SA). The graphene is synthesized by electrochemical exfoliation of graphite at room temperature in 1% sodium dodecyl sulphate (SDS) aqueous solution. Graphene flakes obtained from the process are mixed with polyethylene oxide (PEO) as the host polymer to produce free standing composite thin film which acts as a passive Q-switcher in the TDFL ring cavity. The SA is fabricated by sandwiching the graphene thin film between two fiber connectors. At 1552 nm pump power of 498 mW, a stable pulse train has been observed with a repetition rate of 6.51 kHz and pulse duration of 11.51 µs. The high performances of Q-switched laser suggest that the new type of saturable absorber based on electrochemical exfoliation in conjunction with all-fiber ring cavity configuration is suitable for a Q-switcher near 1900 nm wavelength.